Ozone Chemistry During the 2002 Antarctic Vortex Split - Grooß, J.-U.; Konopka, Paul; Müller, R. (Journal of the Atmospheric Sciences, 2005)
In September 2002, the Antarctic polar vortex was disturbed, and it split into two parts caused by an unusually early stratospheric major warming. This study discusses the chemical consequences of this event using the Chemical Lagrangian Model of the Stratosphere (CLaMS). The chemical initialization of the simulation is based on Halogen Occultation Experiment (HALOE) measurements. Because of its Lagrangian nature, CLaMS is well suited for simulating the small-scale filaments that evolve during this period. Filaments of vortex origin in the midlatitudes were observed by HALOE several times in October 2002. The results of the simulation agree well with these HALOE observations. The simulation further indicates a very rapid chlorine deactivation that is triggered by the warming associated with the split of the vortex. Correspondingly, the ozone depletion rates in the polar vortex parts rapidly decrease to zero. Outside the polar vortex, where air masses of midlatitude origin were transported to the polar region, the simulation shows high ozone depletion rates at the 700-K level caused mainly by NO, chemistry. Owing to the major warming in September 2002, ozone-poor air masses were transported into the midlatitudes and caused a decrease of midlatitude ozone by 5%-15%, depending on altitude. Besides this dilution effect, there was no significant additional chemical effect. The net chemical ozone depletion in air masses of vortex origin was low and did not differ significantly from that of midlatitude air, in spite of the different chemical composition of the two types of air masses.